LIFE CYCLE OF Lincus Tumidifrons Rolston (Hemiptera: Pentatomidae), VECTOR OF THE MARCHITEZ SORPRESIVA IN OIL PALM. - ALVAÑIL-ALVAREZ, FANNY (Revista Colombiana de Entomología, 1993)
In Latín America a bug of the genus Lincus has been reported as the main vector of the protozoan Phytomona sp. causal agent of the "Marchitez Sorpresiva". As a result of its lethal and irreversible nature, this disease has caused enormous economic losses in several oil palm plantations. In Colombia L. tumidifrons Rolston is associated with 90% of the cases of Marchitez. This species has been found on palm trees with Marchitez Sorpresiva in the Llanos Orientales (Meta and Casanare). Norte de Santander and Magdalena. The stages of egg, nymph, and adult are generally found at the leaf bases of fronds 12-33 of trees ranging from 6 months to 20 years of age but the highest incidence is between 4 and 5 years of age. After field and laboratory experiments using different rearing chambers. diets (mainly natural) and microhabitats a colony was established under controlled laboratory conditions (T=24-26°C; R.H.=65-80%). The diet based on Costus amazonensis stems, Renealmia sp. stems and fruits, and Zea mays stripped cobs were used. An average incubation period of 7.81 days was determined. The duration of the nymphal instars was : 1=1.35 days; 11=22.5; 111=33.0; IV=33.7 and V=71.6. The total duration of the nymphal stage was on average 170.2 days. In the chambers, the black color had a positive effect on the development of the life cycle. The highest number of adults was obtained with black, followed by dark green and blue. In light color and transparent chambers, nymphs reached the fifth instar and died.